BURST FAULT ANSLYSIS AND IMPROVEMENT OF A FUEL TANK COVER - ZHANG Feng; REN YiZhi; ZHOU Cheng (Jixie qiangdu, 2021)
According to the burst fault of a fuel tank cover,the failure mode was determined to be fatigue fracture based on the fracture morphology and failure analysis. By contrasting the different of design drawing and using finite element analysis method,the fault mechanism was located through troubleshooting process. The fracture position of the cover was determined to be the maximum stress position. Insufficient thickness of the cover is the fundamental cause of the fatigue resistance. According to the design drawing,the thickness of the cover increased from 3 mm to 4 mm meet the use requirements under the condition that the total height of the cover remains unchanged. The results of the study were recognized by the customer and the improvement measures ensured the safety and reliability of the aircraft in service.